2017
DOI: 10.1080/02640414.2017.1282619
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Talent Development Environment Questionnaire with Chinese talented athletes

Abstract: The development of talented athletes is a priority for many countries across the world, including China. A validated Chinese 5-factor Talent Development Environment Questionnaire (TDEQ-5) would go some way in helping researchers and practitioners investigate talent development systems within China from an evidence-based perspective. For this purpose, the 25-item English TDEQ-5 was translated to Chinese through a standardised process. The translated scale was then administered to 538 talented Chinese youth athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
6
26
1
Order By: Relevance
“…Adequate convergent and discriminant validity was found within three of the of the TDEQ-5 subscales (i.e., COM, HQP and SN), but not for the LTF and AOE subscales. Findings were partially consistent with previously published research that have confirmed the validity of the scale in young talented athletes [14,16,17]. In fact, acceptable construct validity has been reported within both the English and Chinese versions of the TDEQ-5 [14,16].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Adequate convergent and discriminant validity was found within three of the of the TDEQ-5 subscales (i.e., COM, HQP and SN), but not for the LTF and AOE subscales. Findings were partially consistent with previously published research that have confirmed the validity of the scale in young talented athletes [14,16,17]. In fact, acceptable construct validity has been reported within both the English and Chinese versions of the TDEQ-5 [14,16].…”
Section: Discussionsupporting
confidence: 91%
“…Findings were partially consistent with previously published research that have confirmed the validity of the scale in young talented athletes [14,16,17]. In fact, acceptable construct validity has been reported within both the English and Chinese versions of the TDEQ-5 [14,16]. Similar findings of acceptable convergent and discriminant validity were found in the Spanish version of the TDEQ-5 within 322 regional level athletes [17].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations